2019
DOI: 10.3390/cells9010017
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Gene Expression and Beyond—Novel Aspects of Cellular Physiology

Abstract: Mitochondria are peculiar organelles whose proper function depends on the crosstalk between two genomes, mitochondrial and nuclear. The human mitochondrial genome (mtDNA) encodes only 13 proteins; nevertheless, its proper expression is essential for cellular homeostasis, as mtDNA-encoded proteins are constituents of mitochondrial respiratory complexes. In addition, mtDNA expression results in the production of RNA molecules, which influence cell physiology once released from the mitochondria into the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 217 publications
(254 reference statements)
0
30
0
Order By: Relevance
“…In previous studies, it was shown that PolG is a mitochondrial DNA polymerase, which plays an important role in maintaining the stability of mitochondrial DNA. The abnormality of PolG could directly affect the function of the respiratory chain which is composed of proteins synthesized by transcription of mitochondrial DNA and downstream signal modulation of cellular metabolism [19][20][21]. It has also been reported that PolG promotes metabolic reprogramming in various types of tumor cells by affecting mitochondrial function in tumor cells [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was shown that PolG is a mitochondrial DNA polymerase, which plays an important role in maintaining the stability of mitochondrial DNA. The abnormality of PolG could directly affect the function of the respiratory chain which is composed of proteins synthesized by transcription of mitochondrial DNA and downstream signal modulation of cellular metabolism [19][20][21]. It has also been reported that PolG promotes metabolic reprogramming in various types of tumor cells by affecting mitochondrial function in tumor cells [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial gene expression has been recently reviewed by Kotrys et al Transcription initiation sites are located within the D-loop region of both heavy chain (H, rich in guanine) and light chain (L, rich in cytosine). H chain is a template for the transcription of the majority of mitochondrial genes [90]. Transcription of the L chain results mostly in non-coding RNAs, which are degraded by mitochondrial degradosome (a complex of polynucleotide phosphorylase (PNPT1) and ATP-dependent RNA helicase (SUV3).…”
Section: Fusion/fission Systemsmentioning
confidence: 99%
“…On the other hand, new factors are described as engaged in the transcription e.g., mitochondrial ribosomal protein L7/L12 (MRPL12) or mitochondrial transcription rescue factor 1 (MTRES1), which is also involved in translation through binding to the mitochondrial ribosome. New findings indicate that mitochondrial gene expression processes are yet to be fully understood [90]. Translation in mitochondria consists of standard stages of initiation, elongation, termination, and recycling.…”
Section: Fusion/fission Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial diseases are a group of clinically heterogeneous disorders caused by dysfunction of the oxidative phosphorylation (OXPHOS) system and can arise due to defects in genes in the nuclear or mitochondrial DNA (nDNA and mtDNA, respectively) [ 1 ]. Human mtDNA contains 37 genes encoding 13 subunits of the OXPHOS complexes I, III, IV, and V and two ribosomal RNAs (rRNA) and 22 transfer RNAs (tRNAs) crucial for their translation [ 2 ]. The remaining components of mtDNA replication, transcription, and translation processes, including tRNA maturation, initiation and elongation factors, ribosomal proteins, and aminoacyl-tRNA synthetases (mt-aaRSs), are encoded by nDNA, synthesized in the cytosol, and imported into the mitochondria [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%